LANGUAGE-LEARNING FOR BETTER TEACHING-LEARNING EXPERIENCE: FINDINGS AND IMPLICATION - Gordon Deans Dkhar (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
Outlining the problems faced by language learners in the Educational scenario is one key aspect that requires immediate attention in the present era and innumerable studies have indicated that success or failure of students in education is directly or indirectly related to language learning. Ideologically, the different social, political, economic and linguistic aspects individually and collectively played an important role in shaping the quantity and quality of the educational system. However, as a medium of informational exchange between students and teachers, language enters the most vital tool that directly or indirectly influences quality education. The concern therefore attempts an empirical study on students learning English as a second/third language; the socio-psychology of learning English language and the role of attitude and motivation towards language learning vis-à-vis the teaching-learning experiences in the classroom setting. The corpus of the study is elicited from four institutions in Shillong viz. St. Edmunds in Laitumkhrah, St. George in Nongmynsong, Government Boys in Jaiaw and Church of God in Mawlai. The findings in this study will perhaps throw light on the importance of language learning in the educational scenario and how successful language learning underscores better teaching-learning processes and hence quality education. Keywords: Shillong, Language Learning, Education, Socio-Psychology